Think like a Designer – Act like an Anthropologist: Exchange between two Disciplines - Topp, Sebastian (Hamburger Journal für Kulturanthropologie (HJK), 2019)
Der Artikel hat zum Ziel die Mehrwerte eines interdisziplinären Austauschs zwischen kulturanthropologischen Forschungen und Designprozessen zu diskutieren. Diese sollen im Hinblick auf ihr Potential für neue Forschungsansätze diskutiert werden. Das Ziel ist, die zunehmende Komplexität sozialer und kultureller Forschungskontexte stärker zu berücksichtigen und ihre Anwendbarkeit im Hinblick auf eine stadtethnografische Designforschung kritisch zu reflektieren. The article introduces various approaches, which discuss added values in an interdisciplinary exchange between cultural anthropology research and design processes. This is intended to generate potentials for new research approaches that take greater account of the increasing complexity of social and cultural research contexts and provide more open approached to new research contexts. The various approaches are reflected with regard to an example of an urban anthropological design project.